Staphylococcus sp. em profissionais de áreas de apoio de uma instituição oncológica da região Centro-Oeste - VILEFORT, Larissa Oliveira Rocha (2011)
In health care working environment is considered unhealthy by grouping users in one place with a wide variety of diseases and microorganisms such as Staphylococcus sp. It is noteworthy that some species such as Staphylococcus aureus and coagulase-negative staphylococci (CoNS) are known for their virulence, pathogenicity and potential for antimicrobial resistance, may colonize professionals such as areas for support (PAA) and patients. Added to this the greater vulnerability of patients with cancer before the colonization by these microorganisms. It is necessary to use security measures such as standard precautions in order to protect patients and professionals. The objective of this study was to identify the prevalence of Staphylococcus sp. in PAA in the oncology department, as an important route of dissemination of this bacterium at the institutional and community levels. This is a descriptive epidemiological study, developed with PAA of oncology hospital of the Midwest region. Data were collected through a questionnaire and then collected a saliva sample from each participant, which were processed and identified according to standard procedures. It was found that 37.7% of PAA were colonized by Staphylococcus sp., total of 59 isolates, most CoNS. It found a high prevalence (35.0%) of CoNS oxacillin-resistant, and the production of fibrinolysin and lecithinase by S. aureus. Noteworthy is the lack of indication of Personal Protective Equipment (PPE), use the same uniform in different health institutions, the habit of nail biting and the use of ornaments as predictors for occupational exposure to these professionals. It is believed that the perception of PAA about the risk of colonization by microorganisms such as Staphylococcus sp. is of paramount importance to understand the need to adopt safer attitudes at work, aiming at the quality of care and work life.